2017
DOI: 10.1590/2175-7860201768527
|View full text |Cite
|
Sign up to set email alerts
|

Inventário florístico de um remanescente de Floresta Estacional Semidecidual no Sul do Espírito Santo, Brasil: Parque Estadual Cachoeira da Fumaça

Abstract: Resumo Um inventário florístico de espécies de angiospermas provenientes do Parque Estadual Cachoeira da Fumaça (PECF), Espírito Santo, Brasil é apresentado. O PECF está localizado na divisa dos municípios de Alegre e Ibitirama, situado na região do Caparaó, sul do Espírito Santo, protegendo nascentes e remanescentes de um trecho conservado do rio Braço Norte Direito. Objetivou-se com este trabalho ampliar o conhecimento da diversidade de angiospermas de um remanescente de Floresta Atlântica localizado no Sul … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Among the families with the highest number of individuals are Fabaceae with 366, followed by Malvaceae and Cannabaceae with 35, Piperaceae 29, Anacardiaceae with 27 and Meliaceae with 24 individuals. According to Borges & Azevedo (2017), they described that within their work it was observed that the families with the highest number of species were Fabaceae, Asteraceae, Piperaceae, Rubiaceae, Melastomataceae and Myrtaceae, in addition it was observed that among the families the the only one that is not part of the ten most representative families of the flora of Brazil is the Piperaceae family. Freitas et al 2016), observed that the studied species Piper arboreum Aubl.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Among the families with the highest number of individuals are Fabaceae with 366, followed by Malvaceae and Cannabaceae with 35, Piperaceae 29, Anacardiaceae with 27 and Meliaceae with 24 individuals. According to Borges & Azevedo (2017), they described that within their work it was observed that the families with the highest number of species were Fabaceae, Asteraceae, Piperaceae, Rubiaceae, Melastomataceae and Myrtaceae, in addition it was observed that among the families the the only one that is not part of the ten most representative families of the flora of Brazil is the Piperaceae family. Freitas et al 2016), observed that the studied species Piper arboreum Aubl.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Our fragments did not show evidence of severe disturbance, such as selective logging or the passage of fire, although cattle had apparently grazed some areas. However, they presented invasions by exotic species, such as the abundant Coffea arabica (coffee) in the understory stratum (Nunes et al 2003, Borges & Azevedo 2017. The coffee is a biological problem also observed in other semideciduous Atlantic Forest sites (Durigan et al 2000, Martins & Rodrigues 2002, Borges & Azevedo 2017, raising concern how this species interferes with the natural succession processes (Raymundo et al 2018), and may suggest that probably there were coffee plantations in nearby areas or in the same area in the past.…”
Section: Discussionmentioning
confidence: 99%
“…4). According to Borges and Azevedo (2017) the PECF is compose by several phytophysiognomies, such as rocky vegetation, herbaceous swamp, fragments in the initial, medium and advanced stage of regeneration, exotic vegetation and agriculture areas. In addition, the presence of several exotic species, with high invasive potential, present threats to the conservation of native species of the PECF vegetation that has environments in regeneration.…”
Section: Taxonomic Treatmentmentioning
confidence: 99%